Respostas
respondido por:
4
Resposta:
Explicação passo-a-passo:
= 5x/(x^2-2xy+y^2) • 3x-3y/2
= x^2-2xy+y^2
= x^2 - xy - xy + y^2
= x.(x-y) - y.(x- y)
= (x-y).(x-y)
= 5x/(x-y).(x-y) • 3.(x-y)/2
= 3.5x/2 • (x-y)/(x-y).(x-y)
= 15x/2 • 1/(x-y)
= 15/2.(x-y)
= 15x/2x-2y
R.:
15x/(2x-2y)
D)
(x^2 - 1)/(x^2-2x+1)
---------------------------
(X^2+2x+1)/(x-1)
Parte de cima:
(x+1).(x-1) /(x^2 - x - x + 1)
(x+1).(x-1)/ x.(x-1) - 1.(x-1)
(x+1).(x-1)/(x-1).(x-1)
(x+1)/(x-1)
Parte de baixo:
(X^2+2x+1)/(x-1)
(x^2+x+x+1)/(x-1)
x.(x+1)+1.(x+1)/(x-1)
(x+1).(x+1)/(x-1)
= (x+1)/(x - 1) : (x+1).(x+1)/(x-1)
= (x+1)/(x-1) • (x-1)/(x+1).(x+1)
= (x-1)/(x-1) • (x+1)/(x+1).(x+1)
= 1 . 1/(x+1)
= 1/(x+1)
R.:
1/(x+1)
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás